Analisis Prinsip Good Corporate Governance (GCG) pada PT. Sari Amerta Utama Denpasar - Ana Amaliyah Putri; Sumriyah Sumriyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
In running a company, you need principles that make a company good and run according to the rules. This research is in the form of an analysis of the application of Good Corporate Governance (GCG) principles at PT. Sari Amerta Utama Denpasar and providing solutions to PT. Sari Amerta Utama Denpasar so as not to violate GCG principles and applicable laws. The results of this research indicate that PT. Sari Amerta Utama Denpasar has violated GCG principles which have been carried out by Shareholders, Directors and Board of Commissioners. In this way, researchers provide a solution in the form of understanding the human resources at PT. Sari Amerta Utama Denpasar, evaluates the company's SOPs or policies, and carries out evaluation activities on the duties, principals and functions of each company organ.